The Influence of Regulations, Religiosity and Literacy on willingness to pay for Zakat of Professional Civil Servants in the Ministry of Religion of East Java Province - Fahrullah, A'rasy; Nikmah, Nur Ziyadatun; Robbani, Abdullah Azzam (Falah: Jurnal Ekonomi Syariah, 2024)
This study aims to determine the effect of regulation, religiosity and zakat literacy on compliance to pay professional zakat of ASN Regional Office of the Ministry of Religion of East Java Province. This research uses a quantitative approach with non-probability sampling technique with purposive sampling method. Research data were taken from primary sources through direct distribution of questionnaires and through google form to respondents. The results of partial test through SPSS found that the regulation, religiosity and zakat literacy has a significant effect on the willingness of Apparatus to pay professional zakat. Further, the results of simultaneous test found that the variables of regulation, religiosity, and zakat literacy have a significant effect on compliance in paying professional zakat. This finding contributes to the development of a more comprehensive theory of zakat compliance, which combines psychological, spiritual, and institutional aspects to support zakat institutions’ performance.